Canadian Children’s Literature: An Alberta Survey - Bainbridge, Joyce; Carbonaro, Mike; Green, Nicole (Alberta Journal of Educational Research, 2005)
This article presents the findings of an online survey administered to Alberta elementary school teachers in 2000-2001. The survey explored the teachers’ knowledge and use of Canadian children’s literature and their thoughts about the role of Canadian literature in elementary school classrooms. Canadian children’s trade books espouse particular images and values that assist young Canadians in developing a sense of their national and personal identities. Respondents expressed their thoughts about the advantages and disadvantages of using Canadian literature. Overall, most teachers appeared to be unfamiliar with contemporary Canadian books and included Canadian materials in their classroom instruction only for specific Canadian content.